2019
DOI: 10.22487/j24428744.2019.v5.i2.13935
|View full text |Cite
|
Sign up to set email alerts
|

Toksisitas Ekstrak Etanol dan Ekstrak Air dari Daun Jotang Kuda (Synedrella nodiflora (L.) Gaertn.), Daun Gandarusa (Justicia Gendarussa Burm.F.), dan Daun Pulutan (Urena lobata L.) dengan Brine Shrimp Lethality Test

Abstract: Jotang kuda (Synedrella nodiflora (L.) Gaertn.), gandarusa (Justicia gendarussa Burm.f.) and pulutan (Urena lobata L.) leaves are used by several tribes in Central Sulawesi for the treatment of cancer. This study aims to determine the value of LC50 (Lethal Concentration 50) of ethanol and water extracts from the S. nodiflora, J. gendarussa and U. lobata leaves and identify the class of chemical compounds contained in extracts with the highest toxicity. The ethanol extract was obtained by the maceration method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Nitrogen fertilizer indicated a significant difference between the different concentrations, and increasing its concentration resulted in higher sugar content in leaves, as nitrogen is essential for ADP-glucose pyrophosphorylase involved in starch biosynthesis. Widodo et al (2019) reported that applying nitrogen fertilizer to Pennisetum purpureum could increase its total digestible nutrients, such as protein and carbohydrates. Zhang et al (2021) also reported a similar result which showed an increase in sucrose and sorbitol levels in crabapple shoots due to a high concentration of nitrogen Chang and Zhu (2017) revealed that low nitrogen fertilizer concentration caused the cells to be unable to increase the size of leaves cell.…”
Section: Total Sugar Contentmentioning
confidence: 99%
“…Nitrogen fertilizer indicated a significant difference between the different concentrations, and increasing its concentration resulted in higher sugar content in leaves, as nitrogen is essential for ADP-glucose pyrophosphorylase involved in starch biosynthesis. Widodo et al (2019) reported that applying nitrogen fertilizer to Pennisetum purpureum could increase its total digestible nutrients, such as protein and carbohydrates. Zhang et al (2021) also reported a similar result which showed an increase in sucrose and sorbitol levels in crabapple shoots due to a high concentration of nitrogen Chang and Zhu (2017) revealed that low nitrogen fertilizer concentration caused the cells to be unable to increase the size of leaves cell.…”
Section: Total Sugar Contentmentioning
confidence: 99%